Disclosure of risks and opportunities in the integrated reports of South African banks - Khuthadzo Ramabulana; Riyad Moosa (Journal of Risk and Financial Management, 2022)
This study examined the disclosure of risks and opportunities in the integrated reports (IRs) of the top five banks in South Africa. It assesses whether the risk and opportunity disclosures provided comply with the requirements of the International Integrated Reporting Framework (IIRF), as well as the nature of the risks and opportunities disclosed in the IR. This study takes a qualitative approach and employs an interpretivist paradigm. The information for this study was obtained through content analysis of the individual banks' latest available IRs. A checklist was created as a measuring tool to evaluate disclosure practices. The findings showed that three of the selected banks disclosed all the requirements contained in the IIRF regarding risks and opportunities, while two banks only partially complied as they did not provide disclosures about their opportunities. The findings concerning the nature of risk disclosures show that the selected banks disclosed 38 themes related to risks, and the findings concerning the nature of opportunity disclosures show that the selected banks disclosed 14 themes related to opportunities. Furthermore, the results show that those in charge of preparing the IRs provide a thorough disclosure of risks, while there is room for improvement concerning disclosure of opportunities.
Keywords: 650; content analysis; financial institutions; qualitative research; corporate risk reporting